Prostate tumor specific peptide–peptoid hybrid prodrugs. Issue 14 (15th July 2015) - Lee, Jiyoun; Huang, Wei; Broering, James M.; Barron, Annelise E.; Seo, Jiwon
Graphical abstract: Abstract: Inspired by naturally occurring host defense peptides, cationic amphipathic peptoids provide a promising scaffold for anti-cancer therapeutics. Herein, we report a library of peptide–peptoid hybrid prodrugs that can be selectively activated by prostate cancer cells. We have identified several compounds demonstrating potent anti-cancer activity with good to moderate selectivity. We believe that these prodrugs can provide a useful design principle for next generation peptide–peptoid hybrid prodrugs.